Spin-polarized oxygen evolution reaction under magnetic field - Xiao Ren (Nature Portfolio, 2021)
Here, authors demonstrate the ferromagnetic catalyst to facilitate spin polarization in water oxidation reaction. They find the ferromagnetic-exchange-like behaviour between the ferromagnetic catalyst and the adsorbed oxygen species.